Dysphemisms and language change in ZANU-PF and MDC political discourse - Dziya, Dr Hlamba (IJRDO- Journal of Educational Research, 2017)
The aim of this paper is to explore dysphemisms that are used by the Zimbabwe African National UnionPatriotic Front, (ZANU-PF) and the Movement For Democratic Change (MDC) politicians in sixZimbabwean newspapers before and after the signing of the SADC mediated Global Political Agreement(GPA) that ended the political deadlock between the parties in 2008. In this study, I argue that after thesigning of the GPA, political discourse between the parties does not only change considerably, but it alsobecomes progressively and markedly more dysphemistic and more combative in nature than was thecase before the GPA was signed. I hold the view that linguistic analysis of this genre of political discoursemight shed light on the psychology of those who use it.